Fructose 1, 6‐diphosphate regulates desmosomal proteins and collagen fibres in human skin equivalents. Issue 12 (December 2013) - Choi, Hyun; Yang, Seung Ha; Bae, Il‐Hong; Park, Ju‐Yearl; Kim, Hyoung‐June; Noh, Minsoo; Lee, Tae Ryong; Shin, Dong Wook
Abstract We previously reported that fructose 1, 6‐diphosphate (FDP), a glycolytic metabolite, alleviates ultraviolet B‐induced oxidative skin damage. Here, we further examined the effects of FDP on skin. FDP decreased the number of desmosomes, whereas it increased collagen fibres in skin equivalents (SEs). FDP significantly decreased the expression of corneodesmosomal components such as desmoglein 1 (DSG1), desmocollin 1 (DSC1) and corneodesmosin (CDSN), and desquamation‐related proteases, kallikrein 5 (KLK 5) and kallikrein 7 (KLK7) in normal human epidermal keratinocytes (NHEKs). In addition, FDP treatment increased the phosphorylation of p38 MAPK, but the decreased expression of corneodesmosomal components is not recovered by the treatment of p38 MAPK inhibitors. Interestingly, FDP diminished the amplitude of Ca2+ fluxes through down‐regulation of SERCA2. Taken together, these results suggested that FDP induced a decrease in desmosomes and an increase in collagen fibres similar to the process of chemical peeling, the most common treatments for ageing skin.